Disclosing the undisclosed: Commercial paper as hidden liquidity suffers - Sven Klingler; Olav Syrstad (Norges Bank, 2021)
Using new transaction-level data for non-financial commercial paper (CP) in the U.S., we show that companies systematically reduce their outstanding short-term debt on quarterly and annual disclosure dates. Constraints on CP lending supply cannot explain this pattern. Instead, companies optimize their disclosed liquidity buffers and strategically repay CP debt if doing so strengthens common accounting ratios, such as the current ratio. Unlike other CP issuers, firms that repay their CP debt neither hold lower cash buffers nor use CP as bridge financing, suggesting an alternative role of CP debt as "hidden liquidity buffer".
hdl:11250/2835493
Keywords: G32; G23; G14; 330; Commercial paper; balance sheet management; disclosure; cash management; window dressing